Fixing Students’ Pronunciation Using Songs - Ahmad Idris Asmaradhani; Rindawanto Evendi; Ahmad Mursid; Ruslan Abdul Gani (Universitas Pendidikan Mandalika, 2019)
As a Foreign Language, English is difficult for secondary school students in Indonesia not only in terms of grammatical systems but also in terms of phonetic systems. They find it difficult to pronounce most of the English words because in English there is no regular systems of how to pronounce the English words. For EFL/ESL learners in general, to pronounce the English words intelligibly they must refer to a standard dictionary which also means they have to understand how to use and read the dictionary systematically. To understand and improve the production of the various sounds and the supra-segmental features of English as a foreign language, it is suggested to use English songs. This research paper is discussed descriptive-qualitatively based on the authors’ experience as a foreign language learners and teachers. It is discussed how using songs in the English classroom can help students fix their English pronunciation. Supported with a simple questionnaire given to secondary school students, it is also found that most students can fix their pronunciation and they have a strong interest in listening and understanding popular English songs.